Hybrid Organic‐Inorganic Biosensor for Ammonia Operating under Harsh Physiological Conditions. (19th July 2014) - Kumar, Tatikonda Anand; Capua, Eyal; Tkachev, Maria; Adler, Samuel N.; Naaman, Ron
<x xml:space="preserve">Abstract</x> A biosensor for ammonia is developed aimed at detecting the presence of H. pylori bacteria in gastric fluids. The sensor is based on a GaAs device coated with a unique functional polymer that enables high device sensitivity to low concentrations of ammonia and long‐term protection in harsh environments. The detection of ammonia in gastric fluids taken from patients is possible by covering the device with a dialysis membrane, thus enabling the diffusion of only small molecules to the sensing area, while preventing agglomeration of macromolecules on the surface of the device. The mechanism by which ammonia is detected is investigated and an analytical expression is provided relating the response of the detector to the ammonia concentration and the pH of the solution.